2023
DOI: 10.1038/s12276-023-01043-8
|View full text |Cite
|
Sign up to set email alerts
|

Reversing pancreatic β-cell dedifferentiation in the treatment of type 2 diabetes

Jinsook Son,
Domenico Accili

Abstract: The maintenance of glucose homeostasis is fundamental for survival and health. Diabetes develops when glucose homeostasis fails. Type 2 diabetes (T2D) is characterized by insulin resistance and pancreatic β-cell failure. The failure of β-cells to compensate for insulin resistance results in hyperglycemia, which in turn drives altered lipid metabolism and β-cell failure. Thus, insulin secretion by pancreatic β-cells is a primary component of glucose homeostasis. Impaired β-cell function and reduced β-cell mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 102 publications
(150 reference statements)
1
3
0
Order By: Relevance
“…6f) and PDX1 (Fig. 6g) were both downregulated at the mRNA level in human islets exposed to glucolipotoxicity, consistent with the previously reported de-differentiation phenotype pertinent to β-cell demise (75)(76)(77)(78). Yet, in the presence of 43 this de-differentiation was prevented (Fig.…”
Section: Effect Of Stabilizers On Chrebp Downstream Genes and Preserv...supporting
confidence: 89%
“…6f) and PDX1 (Fig. 6g) were both downregulated at the mRNA level in human islets exposed to glucolipotoxicity, consistent with the previously reported de-differentiation phenotype pertinent to β-cell demise (75)(76)(77)(78). Yet, in the presence of 43 this de-differentiation was prevented (Fig.…”
Section: Effect Of Stabilizers On Chrebp Downstream Genes and Preserv...supporting
confidence: 89%
“…Persistent hyperglycaemia is a clinical manifestation of T2D. Reports have linked elevated blood glucose to insulin insufficiency, which could result from pancreatic β-cell mass reduction and peripheral tissues and cells’ inability to respond to insulin action [ 41 , 42 , 43 ]. It was observed in our study that untreated diabetic rats showed elevated blood glucose ( Figure 4 ) with low-serum insulin ( Table 2 ) and sullen pancreatic morphology ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to AKT, phosphorylation of FoxO1 by inflammatory pathways like c-Jun N-terminal kinase (JNK) augments nuclear entry of FoxO1 to increase insulin transcription via upregulation of NeuroD and MafA transcription factors ( 163 , 164 ). Moreover, studies indicates that as insulin resistance and OS progresses, FoxO1 acts to combat these conditions but over time its protein levels decline causing β-cell dedifferentiation and marking a molecular switch to T2D pathology ( 165 , 166 ). Furthermore, the GLP-1RA exenatide decreases inflammation and boosts β-cell function by improving the balance between CD4+ T-helper 17 (Th17) cells and regulatory T-cells (Tregs) ( 167 ).…”
Section: Foxo1 and T2d – Pancreatic β-Cellsmentioning
confidence: 99%